Effects of anxiety sensitivity and cognitive emotion regulation on risky behaviors in Chinese adolescents - Ang, Ping Jun (2010)
The current study utilized a multi-wave longitudinal design and examined whether the relationship between anxiety sensitivity and engagement in risky behaviors in Chinese adolescents would be mediated by use of adaptive/maladaptive coping strategies. Participants completed initial measures assessing their level of anxiety sensitivity, use of cognitive emotion coping strategies and engagement in risky behaviors. Participants also responded to six repeated measures of risky behaviour during the follow-ups. Results of Multi-level Modelling indicated that two maladaptive coping strategies (namely cognitive processes of Blaming-others and Catastrophizing following negative or unpleasant experiences and events) but none of the adaptive coping strategies mediated the relationship between anxiety sensitivity and risky behavior. Implications for research on cognitive coping strategies, limitations and future directions were discussed.